Reducing Student Apathy in Religious Activities: Islamic Education Strategies for Sustainable Character Development (SDG 4.7) - Marhamah; Nasir; Mowafg Masuwd (Universitas Muhammadiyah Surakarta, 2024)
Objective: This study aims to analyze the implementation of school religious activities, students’ apathy toward participation, and Islamic Religious Education (PAI) teacher strategies in strengthening sustainable character development aligned with SDGs principles, particularly SDG 4.7. Theoretical framework: This research applies the theoretical framework of character education, religious school culture, and humanistic pedagogy within Islamic education. Previous studies indicate that religious activities contribute significantly to moral development, although student participation is often influenced by motivation, family background, peer interaction, and digital lifestyles associated with contemporary SDGs educational challenges. Literature review: The literature review shows that religious activities in schools can shape students' character, but student involvement often varies and is influenced by motivational factors, family, social environment, and digital culture. Methods: This study employed a qualitative descriptive case study approach using interviews, observations, and documentation analyzed through the Miles, Huberman, and Saldaña interactive model. Results: The findings reveal that religious activities were implemented systematically through routine habituation, structured programs, and spontaneous spiritual practices. Nevertheless, several students demonstrated apathetic attitudes caused by internal psychological conditions and external social influences. PAI teachers addressed these conditions through persuasive communication, relational guidance, exemplary behavior, and collaborative educational approaches. Implications: The study implies that strengthening contextual, humanistic, and participatory Islamic education management is essential for sustainable student character formation and achievement of SDGs-oriented educational transformation. Novelty: The novelty of this study lies in its integrative analysis connecting school religious culture, student apathy, teacher intervention strategies, and sustainable character education within the broader framework of SDGs implementation in education sectors.